Concentrações hormonais e desenvolvimento folicular de vacas leiteiras em hipertermia sazonal e aguda - Lew, B.J. [UNESP]; Meidan, R.; Wolfenson, D. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
Avaliaram-se as concentrações hormonais e os parâmetros de desenvolvimento folicular de vacas leiteiras expostas ao calor sazonal e agudo. Dividiram-se os animais em quatro grupos: verão (n=5), outono (n=5), inverno com hipertermia aguda (grupo câmara climática, (CC), n=5) e inverno (n=9). Os animais foram abatidos no sétimo dia após a ovulação, e os parâmetros de desenvolvimento folicular avaliados. O líquido folicular do maior folículo foi aspirado e armazenado para posterior análise de hormônios esteróides e inibina. O número de células da granulosa vivas no verão e no outono foi 40 e 45% respectivamente, menor que no inverno (P<0,05). A concentração de estradiol (E2) no inverno foi 62% maior que no outono (P<0,05) e 34% superior ao grupo verão (P<0,06). Houve um aumento na quantidade de androstenediona no verão em relação aos grupos inverno (P<0,08) e outono (P<0,05). A concentração de inibina foi maior no inverno do que no verão e CC (P<0,05). A exposição ao calor sazonal e agudo modificou os parâmetros de desenvolvimento do folículo e as concentrações hormonais no líquido folicular, podendo explicar em parte a queda nas taxas de concepção no verão.

The present study evaluated the seasonal and acute heat stress on follicular development and steroid and inhibin concentrations in follicular fluid, in bovine dominant follicle. Cows were distributed into four treatments: summer (n=5), autumn (n=5), animals heat stressed during the winter (n=5) and winter (n=9). on day 7 of the estrous cycle, animals were slaughtered and parameters related to follicle development were evaluated. The follicular fluid (FF) was aspirated and stored for further hormonal analysis. During the summer, the number of viable granulosa cells was 40% lower than during the winter, and there was a 45% decrease in this parameter during the autumn (P<0.05). In the winter, estradiol concentration was 62% higher than during the autumn (P<0.05) and 42% higher than during the summer (P<0.06). There was an increase in androstenedione concentration in summer group, when compared to winter (P<0.08) and autumn (P<0.05) groups. Inhibin concentration was higher in winter groups than summer and winter heat stressed groups (P<0.05). Seasonal and acute heat stress altered developmental parameters in dominant follicle and hormonal concentration in follicular fluid, those effects can partially explain the decrease in conception rates during summer.
Hormone concentration and follicular development in dairy cows under seasonal and acute hyperthermia
Keywords: folículo; estresse térmico; esteróide; inibina; reprodução; follicle; heat stress; steroids; inhibin; reproduction